Biossíntese catalisada por Beauveria bassiana ATCC 7159 de um novo flavonóide metilglicosilado potencialmente antioxidante e antifúngico - Japiassu, Kamila Bohne (2018)
Biosynthesis of compounds catalysed by microorganisms is an innovative strategy in the functionalization of natural and synthetic products. The application of microorganisms in the production of new bioactive compounds is presented as a promising tool and a great ally of green chemistry. Studies indicate that the morin has interesting antioxidant and antifungal activities. Thus, the objective of this study is the production of morin derivatives through biosynthesis, and the evaluation of its antioxidant and antifungal activities. To screen and identify the most promising strains, 18 filamentous fungi were selected and aliquots of a spore suspension were transferred to 250 ml Erlenmeyers containing 100 ml of a liquid culture medium (20 g of glucose, 0.5 g of yeast extract, 0.5 g of soy peptone, 0.5 g of NaCl, 0.5 g of K2 HPO4). The microorganisms were incubated at 200 rpm and 28 °C for 65 hours. After growth, 25 mg of morin were solubilized in ethanol and added to each Erlenmeyer. After 96 hours of incubation, extraction and subsequent purification were performed on a silica-filled chromatographic column and preparative chromatography. The obtained derivative was characterized by Nuclear Magnetic Resonance of Hydrogen and Carbon (NMR1H13C) and Mass Spectrometry (MS). In addition, antioxidant, antifungal and cytotoxicity activities were evaluated. The results showed that ten strains were able to catalyze the biosynthesis of up to four morin derivatives. Beauveria bassiana ATCC 7159 was selected to conduct the reaction staggering, where it was possible to obtain three ineded derivatives of the starting compound, leading to the isolation and purification of a methylglycosylated major product, termed morin 4’-O-β-D-(4’’-O-methyl) glucopyranoside. The results obtained through the evaluation of antioxidant and antifungal activities showed a good performance of the evaluated compounds. In addition, the obtained compost showed a low red blood cell cytotoxicity (0.6-1.2%). In silico studies have evaluated potential biological activities for morin and its derivatives. The derivative obtained by biosynthesis catalysed by B. bassiana ATCC 7159 is unprecedented and has good antioxidant, antifungal and low cytotoxicity profiles in red blood cells.